Evaluation of Carboxymethyl Cellulose as an Additive for Selective Protein Removal from Wine - Stephan Sommer (Fermentation)
Achieving protein stability is one of the main objectives before bottling wine. Traditionally, this is accomplished via bentonite fining, but the application has drawbacks and is not the most sustainable practice. A promising alternative was previously identified in modified cellulose, which is approved for tartrate stabilization but, as a side activity, could also help remove protein from wine. This study was designed to evaluate powdered carboxymethyl cellulose (CMC) and a liquid formulation in model wine using bovine serum albumin (BSA) and egg white as model proteins. The solubility of BSA proved to be insufficient, so experiments in wine were conducted with egg white protein only. Low-addition levels of liquid CMC showed the highest protein removal rates in real wine, so final trials were conducted with 13 commercial wines to evaluate the performance in different wine styles. The protein removal rate ranged from 12% to 84%, with an overall average of 57%. While these results do not reach the efficiency of bentonite, CMC is showing promise as an additional stabilization tool for a wide variety of wines. It can stabilize over the entire pH range of wine between 2.9 and 4.1, which is a unique feature of this method.